Why Is The Partial Least Square Important For Tourism Studies - Sari Lenggogeni (The Tourism, Heritage and Recreation Sport Center, Universitas Negeri Padang, 2019)
Although the multiple regression method has been applied to exploratory research on most tourism studies, there is lack of understanding on studies that present a well-justified rationale in choosing a robust statistical tool for data analysis. This research note aims to review why tourism researchers are encouraged to use the Partial Least Squares Structural Equation Modelling (PLS-SEM) method to address this research problem. This article provides rationale, comparisons among techniques for multiple regression-based papers and suggestions for tourism researchers to justify why PLS-SEM is important for exploratory studies.